2016
DOI: 10.1016/j.neuropharm.2016.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin differentially modulates excitatory and inhibitory synaptic inputs to putative sleep-promoting neurons of the ventrolateral preoptic nucleus

Abstract: The role of serotonin (5-HT) in sleep-wake regulation has been a subject of intense debate and remains incompletely understood. In the ventrolateral preoptic nucleus (VLPO), the main structure that triggers non-rapid eye movement (NREM) sleep, putative sleep-promoting (PSP) neurons were shown ex vivo to be either inhibited (Type-1) or excited (Type-2) by 5-HT application. To determine the complex action of this neurotransmitter on PSP neurons, we recorded spontaneous and miniature excitatory and inhibitory pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 56 publications
2
37
0
Order By: Relevance
“…Input to type 2 neurons containing 5-HT 2, 4, 7 receptors, however, is enhanced by 5-HT. Although 2 neurons are inversely influenced by 5-TH, they promotes sleep by involving initiation and maintenance of sleep, respectively (Sangare et al ., 2016). It was also reported that injection of 5-HT receptor 1A agonist increases wake time (Monti and Jantos, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Input to type 2 neurons containing 5-HT 2, 4, 7 receptors, however, is enhanced by 5-HT. Although 2 neurons are inversely influenced by 5-TH, they promotes sleep by involving initiation and maintenance of sleep, respectively (Sangare et al ., 2016). It was also reported that injection of 5-HT receptor 1A agonist increases wake time (Monti and Jantos, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Sangare et al used whole-cell patch clamp and single-cell reverse tran-scription polymerase chain reaction to identify the likely players in serotonin-mediated wake-and sleep-state transitioning. 25 Their data revealed that in the VLPO nucleus, type 1 neurons uniquely express 5-HT1A receptors, which mediate the inhibitory response to serotonin, while type 2 neurons express primarily 5-HT2C receptors. Taken in conjunction with early human and animal data, 26,27 5-HT2C agonists may therefore be of great value to the selective pharmacological induction of physiological sleep.…”
Section: Prowake Circuit Physiology and Molecular Modulatorsmentioning
confidence: 99%
“…Animals were decapitated at ZT-0. Brains were quickly extracted without removing the meninges, and coronal slices (300 µm thick) were cut as previously described 23,24 . Individual slices were then placed in a submerged recording chamber Vascular reactivity.…”
Section: In Vivo Nps Microinjections Into the Vlpo And Sleep Monitoringmentioning
confidence: 99%
“…Indeed, the pipette solution contained a low concentration of Cl -(1 mM), resulting in an ECl of -111 mV. Therefore, inward currents were considered as sEPSCs and outward currents as sIPSCs 24 . Data were filtered at 2 kHz, digitized at 10 kHz and acquired on-line using the pCLAMP 10 (Clampex) software (Axon Instruments).…”
Section: In Vivo Nps Microinjections Into the Vlpo And Sleep Monitoringmentioning
confidence: 99%